THE APPLICATION OF THE DEMONSTRATION METHOD IN INCREASING STUDENT LEARNING OUTCOMES IN PAI COURSES IN MATERIALS OF PROCEDURE OF PURIFICATION - Harahap, Juliana (BRIGHT VISION Journal of Language and Education, 2022)
Teaching and learning activities focus on achieving learning objectives. Anything that includes teaching program tools is absolutely required to support the achievement of learning objectives. The type of research used is a qualitative method with a class action research model (CAR) with the aim of improving student learning outcomes in the learning process. Meanwhile, the subject of this study was addressed to fourth grade students at SD Negeri 112281 Aek kanopan. Data collection tools using techniques and instruments: (1) Observation, to collect data on student results that are seen directly in the activity using the demonstration method with the help of the class teacher. Based on the results of Classroom Action Research conducted by researchers on fourth grade students at SD Negeri 112281 Aek kanopan which have been presented for two cycles, the results of all discussions and analyzes that have been carried out can be concluded as follows: (1) Before applying the demonstration method (pracycle), namely using the Practice Rehearsal Pair method (Practice in pairs) learning outcomes from 14 students only 3 students or 21.42% who completed KKM 70 with an average score of 62.85, while 11 students did not complete or as much as 78.58% , to improve student learning outcomes, the first cycle was carried out by applying the demonstration method. (2) By using the demonstration method on the material for ablution procedures, it can successfully improve student learning outcomes. (3) The results of student completeness increased to 10 students or 71.42% with an average value of 71.42, in the first cycle this was not 100% reaching KKM 70 then continued in the second cycle, in the second cycle mastery became 100% of 14 students with an average value of 95.71. Based on these data the target of achieving 100% completeness has been achieved.